Atonement: Jewish and Christian origins - Botner, Max; Duff, Justin Harrison; Dürr, Simon (William B. Eerdmans Publishing Company, 2020)
Cover -- Title Page -- Copyright -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- Part 1: Critical Issues and the Development of Atonement Legislation in the Hebrew Bible -- 1. Atonement (Christian A. Eberhart) -- Introductory Comments -- General Remarks on Sacrificial Rituals in the Hebrew Bible -- The Hand-Leaning Gesture in the Context of Sacrificial Rituals -- The Reception of Isaiah 52:13-53:12 -- The Death and Resurrection of Jesus (Romans 4:25) -- 2. Sin, Sacrifice, but No Salvation (Deborah W. Rooke) -- The Karet Penalty -- Cut Off-But from What? -- Conclusion -- 3. Atonement beyond Israel (David P. Wright) -- P's ḥaṭṭā't System -- H's ḥaṭṭā't in Numbers 15:22-31 -- Introduction (Numbers 15:22-23) -- Specific Cases (vv. 24-26, 27-29) -- Intentional Sin (vv. 30-31) -- Conclusion -- Part 2: Anthropology, Cosmology, and Mediators in Early Jewish and Christian Atonement Theologies -- 4. When the Problem Is Not What You Have Done but Who You Are (Carol A. Newsom) -- The Origins of the Shift -- Later Second Temple Developments -- Conclusion -- 5. The High Priest in Ben Sira 50 (Crispin Fletcher-Louis) -- Ben Sira 50 -- Hebrew Ben Sira 49:16-50:21 -- Priestly and Temple Service Makes All Present to God -- Priesthood as a Representative Office Summing Up All Reality -- Conclusion -- 6. Get the Story Right and the Models Will Fit (N. T. Wright) -- Introduction: The Distorted Story -- Contours of the Biblical Narrative -- Contours of Jesus's Saving Death -- The Cross in Its Narrative Framework -- Conclusion -- 7. "Seeing," Salvation, and the Use of Scripture in the Gospel of John (Catrin H. Williams) -- Composite Citations -- Composite Allusions -- "Lamb of God" (John 1:29, 36) as a Composite Allusion -- John's "Lifting Up" Sayings-Seeing the Exalted One -- Seeing the Pierced One -- Conclusion.